(untitled) (International Journal of Biology and Chemistry, 2020)
Growing global demand and growth in oil production and refining lead to an increase in environmental pollution by waste from these industries. Huge territories of Kazakhstan are influenced by the activities of the oil and oil refining industries. The consequence of this is the deterioration of ecosystems in the oil-producing regions, the decline in biodiversity and deterioration of public health. In this regard, there is a need in an informative bioindicator for studying the state of ecosystems of oil producing regions. The aim of this research was to evaluate the effects of oil and petroleum products exposure on the function of thyroid gland in tadpoles of local amphibian species. The study revealed that chronic exposure to watersoluble fraction of oil, o-xylene or diesel fuel causes hypertrophy and hyperplasia of the thyroid follicular cells, a decrease in the colloid volume in the follicles, as well as a decrease in the content of thyroid hormones in the tadpoles of the marsh frog (Rana ridibunda) and green toad (Bufo viridis), which indicates a suppression of thyroid function.